2012
DOI: 10.1152/japplphysiol.00869.2012
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary resistance running with short distance enhances spatial memory related to hippocampal BDNF signaling

Abstract: Although voluntary running has beneficial effects on hippocampal cognitive functions if done abundantly, it is still uncertain whether resistance running would be the same. For this purpose, voluntary resistance wheel running (RWR) with a load is a suitable model, since it allows increased work levels and resultant muscular adaptation in fast-twitch muscle. Here, we examined whether RWR would have potential effects on hippocampal cognitive functions with enhanced hippocampal brain-derived neurotrophic factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
69
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 47 publications
9
69
0
1
Order By: Relevance
“…Greenwood et al (2012) showed that running distances increase steadily over time, peak in week 4 and plateau afterwards. Comparing our results to other studies using voluntary exercise, the running distances in our study are comparable to those of Ke et al (2011) and Lee et al (2012). However, compared to those of Griesbach et al (2004b), Hayes et al (2008), Kinni et al (2011) andYau et al (2012), both intensity and distance of our animals are at the lower end.…”
Section: Discussionsupporting
confidence: 81%
“…Greenwood et al (2012) showed that running distances increase steadily over time, peak in week 4 and plateau afterwards. Comparing our results to other studies using voluntary exercise, the running distances in our study are comparable to those of Ke et al (2011) and Lee et al (2012). However, compared to those of Griesbach et al (2004b), Hayes et al (2008), Kinni et al (2011) andYau et al (2012), both intensity and distance of our animals are at the lower end.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, it has been recently reported that the hippocampal lactate derived from glycogen acts to retain memory function, not only as an energy source, but also as a neuromodulator that increases synaptic plasticity [26,27,46]. Indeed, we have reported that a model of chronic high-intensity intermittent exercise using voluntary wheel running enhances the memory function associated with hippocampal structural changes [47,48]. In the present study, we employed a high-intensity intermittent swimming rat as an intense exercise model and found a possible involvement of serotonin in hippocampal glycogenolysis with high-intensity intermittent exercise.…”
Section: Cmentioning
confidence: 91%
“…Kozlovksy et al (23) have reported that PTSD-like behavioral responses are associated with a down-regulation of BDNF mRNA, suggesting that individuals who are experiencing extreme behavioral responses to stress may have an impaired synaptic stabilization and increased sensitivity to an extreme stress response. Exercise has been shown to increase BDNF concentrations (17,24) and has also been suggested to be a mechanism for the depression-relieving effects of exercise (26).…”
mentioning
confidence: 99%